Tujuan Penciptaan Manusia Dalam Kajian Al-Quran - Shofiyah, Nida; Sumedi, Sumedi; Hidayat, Tatang; Istianah, Istianah (ZAD Al-Mufassirin, 2023)
The purpose of this study is to analyze the purpose of human creation in the study of the Quran. This research uses qualitative approach and literature review method. Based on the results of the discussion, humans are seen as a "small universe" (micro-cosmos, al-alam al-shagir) which is a mirror of the great universe (macro-cosmos, al-alam al-kabir). It means that the human self represents or reflects the entire universe or universe. Man has the basic potential of reason and heart, as well as two dimensions within him, namely the physical dimension and the spirit dimension with these provisions man can relate to God and to other beings that God created. In carrying out life on earth, humans have two important roles, namely being servants of God and caliphs. Man as a servant of Allah means obedience, submission and obedience worthy only to Allah. As for in carrying out his Caliphate man needs to prosper and maintain the earth by acting justly towards all creatures on earth.